Geochemistry blocks to predict significant mineral deposits in the Antioquia Department Republic of Colombia Au, Cu, Mn, Mo, Ni, Pb, Zn elements (2007)
The geochemical sampling allows determining the geochemical provinces, defined as an “earth crust portion or segment that has a significant chemical composition different of the average (Rose et al., 1979)”. These researches involve the analysis of a great number of elements that are not commonly considered in traditional exploration studies making recognition of large areas, discovering potential areas for the mining prospection. From the environmental point of view, it is possible to detect elements potentially dangerous for the ecosystems and for the living being’s health. The geochemical studies in Colombia have been developed in three steps: The first was made for the Geological Survey of Colombia (INGEOMINAS) as regional geological survey program, between 1970 and 1992, 1:100.000 scale, taking samples of the stream sediments and using sample techniques of the ultra high density. The second sampling step was made also for INGEOMINAS, applying methodologies of the ultra low density at southeastern region of Antioquia, in which the samples made part of the project “Geochemical survey in the 5 – 09 Map” in 2001. The last phase was carried out for the Faculty of Mines of the National University, using a sampling system of ultra low density; the samples were taken between 2004 and 2006. The aim of this document is to show some results of the geochemical information of the Antioquia Department that contributes to indicate the mineral baseline provinces applied to the resources exploration, mainly for precious and base metals and to establish an environment base line of the territory. In this document are found the results of the geochemical cartography of the Department of Antioquia, 1: 500.000 scale, made for seven elements of the periodic table: Au, Cu, Pb, Zn, Mn, Ni and Mo, through a low and ultra low density sampling (a composite of 600 km 2 ) in stream active sediments. The basic unit of sampling involves cells (panels) of 30 Km x 20 Km, from which 464 samples were obtained and from these 101 representative composites of the regular sampling mesh were conformed. The used techniques for the geochemical analysis were the X Ray Fluorescence (XRF), inductively coupled plasma mass spectrometer (ICPMS), inductively coupled plasma atomic emission spectrometer (ICPOES) and Neutron Activation (INAA). The spatial modeling was carried out utilizing the geostatistical technique of the lognormal kriging, allowing to estimate around 61,7 and 62,8 millions of data and to make the base line for each one of the considered geochemical variables. The geochemical mapping of the Antioquia Department allowed identifying two anomalies for the Cu and Pb elements, and 17 significant local anomalies: six Mn anomalies, four Mo anomalies, five Ni anomalies and two Zn anomalies. The obtained results indicate high mineral potential of the geochemical subblocks and blocks in the unknown mineralizations of the Antioquia Department; some data are 1.8 x 109 ton of Cu, 91 x 106 ton of Pb, 5.6 x 109 ton of Mn, 263 x 106 ton of Ni, 614 x 106 ton of Zn and 12 x 106 ton of Mo and 15.9 x 106 ton of Au. Based on the recognized resources inventory of the department, the mineralization coefficient was determine for Cu (0.0002), Pb (0.003), Mn (0.0003), Ni (0.0004), Zn (0.0009) and Au (0.00008). / Resúmen. El muestreo geoquímico permite la determinación de las provincias geoquímicas, que se define como una "porción de la corteza terrestre o segmento que tiene una composición química diferente significativo de la media (Rose et al., 1979)". Estas investigaciones involucran el análisis de un gran número de elementos que no son comúnmente considerados en los estudios de exploración tradicionales de toma de reconocimiento de grandes áreas, el descubrimiento de áreas potenciales para la prospección minera. Desde el punto de vista medioambiental, es posible detectar elementos potencialmente peligrosos para los ecosistemas y para el ser vivo de la salud. Los estudios geoquímicos en Colombia se han desarrollado en tres etapas: La primera fue hecha por el Instituto Geológico y Minero de Colombia (INGEOMINAS) como el programa regional de estudios geológicos, entre 1970 y 1992, escala 1:100.000, tomando muestras de los sedimentos de corriente y el uso de la muestra técnicas de la densidad ultra alta. El paso segundo muestreo se hizo también para INGEOMINAS, la aplicación de metodologías de la densidad de ultra bajo en la región sureste de Antioquia, en los que las muestras a ser parte del proyecto "estudio geoquímico en el 5-09 Mapa" en 2001. La última fase se llevó a cabo en la Facultad de Minas de la Universidad Nacional, utilizando un sistema de muestreo de ultra baja densidad, las muestras fueron tomadas entre 2004 y 2006. El objetivo de este documento es mostrar algunos resultados de la información geoquímica del Departamento de Antioquia, que contribuye para indicar las provincias de base minerales aplicados a la exploración de recursos, principalmente para los metales preciosos y de base y establecer una línea base del medio ambiente del territorio. En este documento se encuentran los resultados de la cartografía geoquímica del Departamento de Antioquia, 1: 500.000 escala, realizados por siete elementos de la tabla periódica: Au, Cu, Pb, Zn, Mn, Ni y Mo, a través de un bajo y ultra toma de muestras de baja densidad (un compuesto de 600 km 2) en los sedimentos corriente activa. La unidad básica de muestreo consiste en células (grupos) de 30 km x 20 km, de los que 464 muestras se obtuvieron y de estos 101 compuestos representante de la malla de muestreo regular se conformaron. Las técnicas utilizadas para el análisis geoquímicos fueron la Fluorescencia de Rayos X (XRF), el espectrómetro de masas de plasma acoplado inductivamente (ICP-MS), acoplado por inducción espectrómetro de emisión atómica con plasma (ICPOES) y activación neutrónica (INAA). El modelado espacial se realizó utilizando la técnica geoestadística kriging de la lognormal, lo que permite estimar en torno a 61,7 y 62,8 millones de datos y hacer la línea base para cada una de las variables geoquímicas en cuenta. El mapeo geoquímico del Departamento de Antioquia, permitió identificar dos anomalías de los elementos Cu y Pb, y el 17 de anomalías significativas locales: seis anomalías Mn, Mo anomalías cuatro, cinco anomalías Ni y Zn dos anomalías. Los resultados obtenidos indican el potencial mineral de alta de los subbloques geoquímicos y mineralizaciones de bloques en el desconocido del Departamento de Antioquia, algunos datos son 1.8 x 109 toneladas de cobre, 91 x 106 toneladas de Pb, 5.6 x 109 toneladas de manganeso, 263 x 106 toneladas de Ni, 614 x 106 toneladas de zinc y 12 x 106 toneladas de Mo y 15,9 x 106 ton de Au. Con base en el inventario de los recursos reconocidos del departamento, la mineralización coeficiente de determinar para el Cu (0,0002), Pb (0,003), Mn (0,0003), Ni (0,0004), Zn (0.0009) y Au (0,00008).